2020
DOI: 10.48550/arxiv.2010.10746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing inclination dependent analyses of kilonova transients

J. Heinzel,
M. W. Coughlin,
T. Dietrich
et al.

Abstract: The detection of AT2017gfo proved that binary neutron star mergers are progenitors of kilonovae. Using a combination of numerical-relativity and radiative-transfer simulations, the community has developed sophisticated models for these transients for a wide portion of the expected parameter space. Using these simulations and surrogate models made from them, it has been possible to perform Bayesian inference of the observed signals to infer properties of the ejected matter. It has been pointed out that combinin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…Secondly, information on the viewing angle is potentially obtainable from the observation of a relativistic jet, which can improve parameter estimation on systems with asymmetric outflow geometries (see, e.g., Heinzel et al 2021). Currently, the relativistic jet that is launched in some mergers (see, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, information on the viewing angle is potentially obtainable from the observation of a relativistic jet, which can improve parameter estimation on systems with asymmetric outflow geometries (see, e.g., Heinzel et al 2021). Currently, the relativistic jet that is launched in some mergers (see, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In order to better understand modelling errors, our kilonova model cross-comparison should be extended to incorporate parameter inference (see, e.g. Heinzel et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in ejecta properties seen both in simulations and in the analysis of GW170817 have motivated a broad set of additional studies of both ejecta morphology, composition, masses, and velocities (Fontes et al 2020;Tanaka et al 2020;Kawaguchi et al 2020;Krüger & Foucart 2020;Korobkin et al 2020;Barnes et al 2020;Heinzel et al 2020). These sets of detailed kilonova models that cover a broad range of the parameter space are essential in the analysis of kilonova observations.…”
Section: Introductionmentioning
confidence: 99%
“…The joint detection of gravitational waves and electromagnetic signals from the first confirmed neutron star merger observation (GW170817) Abbott et al (2017); Kasliwal et al (2017); Chornock et al (2017); Smartt et al (2017); Soares-Santos et al (2017); Cowperthwaite et al (2017) recently demonstrated the potential power of these systems to study general relativity, nuclear physics, astrophysical nucleosynthesis, and the properties of compact objects. However, theoretical uncertainties in the amount of mass ejected by a given merger Krüger & Foucart (2020) and its composition Wanajo et al (2014); Foucart et al (2018), radiation transport in that ejecta Heinzel et al (2020), the outcome of nucleosynthesis Barnes & Kasen (2013), and the energy that released by nuclear reactions in the ejecta Barnes et al (2016) limit the amount of information that we can extract from merger observations. Numerical simulations of neutron star mergers play an important role in our ability to analyze these systems.…”
Section: Introductionmentioning
confidence: 99%